Arthur Ashe--tennis great - Weissberg, Ted.; King, Coretta Scott 1927-2006. (New York Chelsea House, 1991)
Presents the life of an important black athlete and tennis player, Arthur Ashe.
Includes bibliographical references (p. 106) and index.
Keywords: Ashe, Arthur -- Juvenile literature; Ashe, Arthur; Tennis players -- United States -- Biography -- Juvenile literature; Tennis players; African Americans -- Biography